分权集权 ：地方政府利益机制的变化 = Decentralization and recentralization : changing incentive structures for China's local governments - 赵学明 Zhao, Xueming (2008)
The market reform in China is a complicated system engineering project. But the twenty years of the reform process follows the thread of power changes between the central and local governments and amongst enterprises and individuals. This thesis seeks to analyses the changing incentive structures of China's local governments in the process of decentralization and recentralization of the state power so as to construct a scientific framework for studying the complex system reform in China.